Service Blueprinting to Enhance Restaurant’s Service Process - Dewi, Luciana Triani; Nguyen Thi Chinh; Keren Kerviona (International Journal of Industrial Engineering and Engineering Management, 2022)
Restaurants should provide services that enable satisfy their customers. The study was conducted in a local Taiwan restaurant. The restaurant has been running since 2015 and, so far, has not shown significant progress. Service blueprinting was used to identify where substances could be improved and where customer satisfaction problems occurred. The purposes of the study are (1) to identify the service process by service blueprinting, (2) to find the potential failure points of the existing service process, and (3) to propose possible solutions to the failure points. The results show two categories of potential failures were recognized, i.e., receiving- delivering orders and waiting for food. The substitute order mechanism is proposed as the solution.